Radial head and neck fractures in children and adolescents - Kalbitz, Miriam; Lackner, Ina; Perl, Mario; Pressmar, Jochen (Frontiers in Pediatrics, 2023)
Background Radial head and neck fractures are a rare entity in pediatric patients. Due to specific characteristics of the blood supply and remodeling potential, the correct diagnosis and initiation of appropriate therapy are crucial for the outcome. Therefore, the aim of this retrospective observational study was to present the outcome of a series of pediatric patients with radial head and neck fractures. Methods In total, 67 pediatric and adolescent patients with a fracture of the proximal radius admitted to a Level I Trauma Center (Germany) between 2005 and 2017 were included in this retrospective observational study. Patients were stratified in accordance with the classification of Judet modified by Metaizeau and with the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF). Results AO-PCCF fracture type of proximal radius was age-dependent. Epiphyseal axis angle and displacement angle correlated significantly. Fractures treated with a K-wire or embrochage centromedullaire elastique stable (ECMES) presented higher displacement angles. The duration of callus formation was dependent on both the reduction technique and fracture displacement. The range of motion after complete fracture consolidation was dependent on the Metaizeau type and reduction technique but independent of the duration of immobilization and physical therapy. Conclusion and clinical relevance Both the epiphyseal axis and displacement angle are suitable for measuring the initial fracture displacement in radiographs. Consolidation is dependent on the initial displacement and reduction technique. The mini-open approach leads to a worse reduction result, later callus formation, and a more restricted range of motion in terms of pronation. Furthermore, the range of motion at follow-up is independent of the duration of immobilization and physiotherapy.